H∞ Control of Continuous-Time Linear Systems Using Dynamic and Static Output Controllers - Dusan KROKAVEC; Anna FİLASOVA (International Journal of Applied Methods in Electronics and Computers, 2015)
The paper deals with the problem of the H ∞ control of continuous-time linear systems by proper dynamic output controllers of order equal to the plant model order and by static output controller. The design procedure is based on solution of the set of linear matrix inequalities and the matrix equality and ensures the closed-loop asymptotic stability using Lyapunov approach and the H ∞ performance, to guarantee the closed-loop system robustness to unknown disturbance. Numerical examples are given to illustrate the design procedures and the relevance of the method as well as to validate the performances of the proposed approach.